PENGEMBANGAN MEDIA PEMBELAJARAN BERBANTUAN APLIKASI CANVA PADA TEMA INDAHNYA KERAGAMAN DI NEGERIKU KELAS IV SD - Nurmah Dalizah,; Safrida Napitupulu, (Jurnal Cakrawala Ilmiah, 2024)
This research aims to develop learning media assisted by the Canva application that is suitable for use in the thematic learning process on the theme "The Beauty of Diversity in My Country" in class IV elementary school. This research is development research (Research and Development) using the ADDIE development procedure which consists of 5 stages. The test subjects in this research were media experts, material experts, learning experts and student responses. The object in this research is learning media assisted by the Canva application which is suitable for use in the learning process. The instrument used to collect data was a validation questionnaire given to several expert validators, namely media expert validators, material expert validators and learning expert validators. The total score obtained from validation by media experts was 90.6, from validation by material experts, namely 87.2, from learning experts it was 93.2 and from student responses a score was obtained of 94.2. The average score from the validation results is 91.3. From this score, it can be said that the learning media assisted by the Canva application developed is "very suitable" for use in the thematic learning process in class IV at SD Fauzan Al Islamiyah Medan.